Urban Transport of Passengers in Large Urban Agglomerations and Sustainable Development. Experience of Bucharest Municipality in Romania - Bran, Florina; Burlacu, Sorin; Alpopi, Cristina (European Journal of Sustainable Development, 2018)
Urban transport of passengers is considered in Romania a priority of local communities. Thus, this service, together with four other services (water supply and sewerage, public lighting, sanitation and district heating), is subject to a special law, Law 51/2006, also called the Law on Community Utilities. In 2016 the public utility law was republished, amended and completed by Law 225. Why it was necessary to change and complete the law of public utilities and what role the urban public transport service has in the sustainable development of localities, are questions that we are trying to answer through our research. The proliferation of green transport modalities as well as technological progress have forced paradigm shifts in terms of mobility in large urban agglomerations. A comparative analysis of the public transport modalities in the large urban agglomerations comparable to Bucharest could not be made without considering the socio-economic and environmental factors. Sustainable development of urban transport will help to increase the quality of life for urban residents and regain the well-deserved position of urban transport as a public service of general interest. Keywords: sustainable transport, sustainable development, Bucharest experience